Recognizing promise : the role of community colleges in a post pandemic world - Baston, Michael A.; Bridglall, Beatrice L., 1968-; Nettles, Michael T., 1955- (Great debates in higher education., 2022)
COVID-19 has exposed and exacerbated entrenched inequities spawned by the historical and structural reality of bigotry, prejudice, discrimination, and inequity in all forms, and at institutional and individual levels. It is perceived that higher education institutions also perpetuates these inequities, which is fuelled by prevailing misconceptions, such as "college should be limited to the privileged few"; or that "community colleges are in some way 'inferior'." Recognizing Promise re-establishes the role community colleges can play in reversing centuries of racial and gender disparities in economic wealth, health, education, and life expectancy stemming from current and historical policies and practices that sustain structural racism. The result is a more civic-minded, educated citizenry and a stronger workforce of tomorrow. Educators in the community college space, in partnership with business, industry and philanthropic leaders, can lead the way in reasserting commitment toward eradicating racism and sustaining reform that advocates inclusive excellence, educational access and programmatic diversity, and the alignment of learning with opportunities in the workplace.